Assessing associations between empathy, attitudes towards animal welfare, and stress in dairy farm workers - Curcio, Hannah, author; Stallones, Lorann, advisor; Cramer, Catie, committee member; Dik, Bryan, committee member; Graham, Dan, committee member (Colorado State University. Libraries, 2024)
Livestock farmers face job-specific stressors that increase their overall risk of stress-related diseases and deaths. While the literature suggests a relationship between farm workers' levels of empathy, their own well-being, and the welfare of their livestock animals, little research has adequately investigated these potential associations. Furthermore, empathy towards animals has been linked to attitudes about and indicators of animal welfare, but no previous research had assessed levels of empathy in dairy workers specifically towards their dairy cattle. The present study, thus, assessed the relationships between empathy towards dairy cattle, attitudes towards animal welfare, stress related to the welfare of cattle, and stress pileup in dairy farm workers. Specifically, I hypothesized that dairy workers' levels of empathy towards dairy cattle would be positively correlated with their attitudes towards animal welfare; dairy workers' levels of stress related to the welfare of cattle would be negatively correlated with their levels of empathy towards dairy cattle and their attitudes towards animal welfare; and, dairy workers' stress pileup (as measured by the number of stressors participants reported often caused them stress) would be negatively correlated with their levels of empathy towards dairy cattle and their attitudes towards animal welfare. As hypothesized, dairy workers' stress pileup was negatively correlated with levels of empathy towards dairy cattle. No evidence was found in support of the other hypotheses. However, additional exploratory analyses found relationships between empathy and the following variables: a positive relationship with years working in production livestock, a negative relationship with size of herd, primary language (such that participants with English as their primary language had significantly higher empathy for dairy cattle scores than those with Spanish as their primary language), and birth country (such participants born in the United States had significantly higher empathy for dairy cattle scores than participants born in Mexico). While limited, the results highlight the ways in which the well-being of farm workers and the welfare of their livestock are interconnected and posits that empathy may play a crucial role.
Keywords: empathy; occupational stress; animal welfare; one welfare framework; farmer well-being